Classification of clinical Cutibacterium acnes isolates at phylotype level by capillary electrophoretic methods in roughened fused silica capillary - Horká, Marie; Růžička, Filip; Karásek, Pavel; Šalplachta, Jiří; Siváková, Alena; Roth, Michal (Talanta, 2022)
Despite being commensal bacterium involved in the maintenance of healthy skin, Cutibacterium acnes is also associated with inflammatory diseases. Since inflammatory and immunogenic properties vary between C. acnes phylotypes, reliable classification of clinical C. acnes isolates is important for determining their pathogenicity. Combination of optimized separation methods, polymer-enhanced transient isotachophoresis and sweeping of the charged bacterial cells in micellar electrokinetic chromatography in the roughened fused silica capillary, was used for the separation of twenty clinical C. acnes isolates. Their correct classification into the individual phylotypes was achieved in 20 min at laboratory temperature. In addition, decrease in the separation temperature to 15 °C led to the separation of the individual isolates of some phylotypes. Relative standard deviations of migration times of both intra- and inter-day analyses did not exceed 1.7%. Linearity of the proposed method in the concentration range from 5 × 105 to 1 × 107 cells mL-1 was characterized by the coefficient of determination R2 = 0.9985. Limit of detection of 5 × 105 cells mL-1 (50 cells in 100 nL of the injected sample) was determined for all the examined bacteria.
Keywords: Cutibacterium acnes; oxid křemičitý; micely; Capillary electrophoresis; Silicon Dioxide; kůže; Fused silica capillary; Acne Vulgaris; Humans; Chromatography, Micellar Electrokinetic Capillary; Supercritical water; lidé; acne vulgaris; Micelles; Phylotype; chromatografie micelární elektrokinetická kapilární; Skin; Classification